2018
DOI: 10.1051/matecconf/201822506015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potential Sites for Harnessing Tidal Energy around Coastal Area of Malaysia

Abstract: This paper present the potential sites around coastal area of Malaysia for electricity generation by harnessing tidal energy. As the electricity demand increase over the year and generating electricity by using fossil fuel caused the increase number in CO2 emission, thus renewable energy become one of the solution for alternating energy for electricity. There are a few of identified locations along Malaysia’s coastal area that have potential for tidal energy implementation. The approaching for harnessing tidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…However, it is still rational to study the tidal range energy in Malaysia as some site locations identified have the potential for harnessing tidal range energy. Some sites just barely meet the minimum requirement of tidal range 3 m, so each one needs a large tidal basin area to produce the greatest output power generation [51]. The drawback of a large tidal barrages or lagoons system is that it requires high construction cost, block the movement of fish and other wildlife into and out of the estuaries, and the turbine's rotor can kill wildlife that tries to swim through them [52].…”
Section: A Tidal Range Energymentioning
confidence: 99%
“…However, it is still rational to study the tidal range energy in Malaysia as some site locations identified have the potential for harnessing tidal range energy. Some sites just barely meet the minimum requirement of tidal range 3 m, so each one needs a large tidal basin area to produce the greatest output power generation [51]. The drawback of a large tidal barrages or lagoons system is that it requires high construction cost, block the movement of fish and other wildlife into and out of the estuaries, and the turbine's rotor can kill wildlife that tries to swim through them [52].…”
Section: A Tidal Range Energymentioning
confidence: 99%
“…However, evaluating tidal potential energy within the SCS using data from semi-empirical models has been notably lacking. Existing studies on tidal energy have primarily focused on utilizing Tide Tables, as seen in Yusoff (2015) [27], or at specific measurement points, as illustrated by Lee (2008) [28], Nazri (2018) [29], without delving into the exploration of tidal energy, particularly in terms of potential energy, across the entire SCS. Using data derived from semi-empirical tide models presents an avenue for exploring novel research trajectories and applications within the domain of tidal energy analysis specific to the SCS.…”
Section: Introductionmentioning
confidence: 99%